Perbandingan Data Cuaca Dari Alat Digital dan Konvensional di Stasiun Meteorologi Raja Haji Abdullah-Karimun - Prastio, Bayu; Mardalena, Tri; Dzirrusydi, Zalmi (Jurnal Informasi, Sains dan Teknologi, 2024)
This study compares weather data from conventional and digital measurement tools at Raja Haji Abdullah-Karimun Meteorological Station and evaluates the correlation value between the two. Descriptive quantitative methods were used to analyze weather data from January 2022 to December 2023. Results showed significant differences between weather data from conventional and digital tools. The Mann-Whitney statistical test showed a probability value (sig) less than the set significance level (0.000 < 0.05), indicating a significant difference. This finding highlights the importance of calibrating measurement tools to ensure accuracy and consistency in observations. On temperature and humidity measurements, the Mann-Whitney test showed sufficient statistical evidence to reject the null hypothesis (H0) and accept the alternative hypothesis (H1), stating a significant difference between digital and conventional measurements. In conclusion, this study emphasizes the importance of continuous validation of weather measurement methods as well as the need for adjustment and improvement of measurement tools to ensure reliable results. This research makes an important contribution to the understanding of the comparison of conventional and digital weather measurement tools, which can serve as a basis for the development of future weather observation technologies.